ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT STRES PADA LANJUT USIA DI UNIT REHABILITASI SOSIAL DEWANATA KABUPATEN CILACAP - Suci Khasanah; Wina Mutiara (Universitas Harapan Bangsa Purwokerto, 2013)
The increasing number of elderly will require serious because naturally the elderly has declinedboth in terms of physical, biological, and mental. In addition to degenerative diseases, psychologicalproblems is also an important factor that can affect the lives of the elderly is one of them stress. Theincidence of stress in Indonesia between 2% to 8% on elderly age in comunity, 10% on elderly age inhealth care instituted and 15% for senior citizens in nursing homes. The purpose of the research is toidentify the factors that influence to the stress caused in old age in Social Rehabilitation Unit Dewanatain Cilacap Regency.The research is analytical inferential hypothetical analysis with cross sectionalappoach. The sampling technique used is purposive sampling from 48 senior citizens. The results showedthe factors that influence to the stress level that is not suffering from the disease (58,6%), rarelyexperienced conflict (93,1%), the role of the family enough (89,7%), adequate social support (75,9%)experienced mild levels of stress (60,4%).The summary note in the research showed that all factors beingresearched have influence to the stress level in old age in Social Rehabilitation Unit Dewanata in CilacapRegency. Key words: Stress, Elderly